Existence of solutions for stochastic Navier-Stokes alpha and Leray alpha models of fluid turbulence and their relations to the stochastic Navier-Stokes equations - Sango, Mamadou (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.